Why Do the Citizens Trust the Police? - Mukhametov, Ruslan (Sotsiologicheskoe Obozrenie / Russian Sociological Review, 2024)
This study is devoted to the investigation of factors affecting the level of trust in the Russian police. The main research issue of the article is to understand why some citizens trust law enforcement agencies, while others do not. To achieve this goal, data obtained during the 7th wave of the World Values Survey were used. The method of analyzing quantitative data was ordinal logistic regression. It is shown that the crime rate in the area of residence and the perception of security have received only partial empirical confirmation. The positive influence of the perception of corruption on trust in the police was found. The article also portrays how a more favorable attitude towards law enforcement agencies is associated with higher corruption. The author comes to the conclusion that citizens with higher levels of trust generally have more positive attitudes towards law enforcement agencies. It has been established that the level of trust of post-materialists in the police is lower than that of materialists. Statistical analysis has shown that an increase in the number of citizens with post-materialistic values leads to a decrease in the level of trust in law enforcement agencies. The author found that men have a lower level of trust in the police compared to women. The significance of the study lies in the fact that it can provide useful and practical recommendations for improving the work of the police and increasing the level of public confidence in it.